A cross layer protocol to mitigate effects of radio's linear impairments. (2017) - Samant, Abhay; Yadav, Sandeep Kumar; Badarla, Venkataramana; Mishra, Shirish
The impact of signal-to-noise ratio (SNR) of an additive white Gaussian noise (AWGN) channel on bit error rate (BER) has been extensively studied in the literature through theoretical, simulation-based, and experimental results. However, it is too simplistic to assume that BER in a real-world communication system is influenced by AWGN alone. The system's radio, which contributes both linear and nonlinear impairments, also impacts BER. This paper studies the impact of linear impairments, namely quadrature skew and gain imbalance, on the BER of an angular digital modulation scheme, such as M-ary phase shift keying (M-PSK). It presents a mathematical derivation of a technique to measure these impairments. It implements this technique on an experimentation system and presents statistical properties of these measurements. A novel contribution of this paper is a cross layer protocol through which the receiver shares these measured values with the transmitter. The transmitter uses this information to combat the effects of radio's impairments on BER, thereby improving system performance. This paper also presents a cost benefit analysis which proves that the idea proposed in this paper is feasible and practical to implement on real-world systems.